Analisa Korelasional terhadap Motivasi dan Kinerja Tim Pelayanan Kesehatan Peduli Remaja di Unit Kesehatan Remaja - Riska Febrilia Dewi; Sulaimi Putra; Dhita Kurnia Sari (Jurnal Akademika Baiturrahim Jambi, 2022)
The low motivation may decrease the health professional performance. Work motivation and teamwork performance may affect the capacity of the labor contribution. Motivation will also increase the effort and enthusiasmto achieve the high productivity. The purpose of this study was to determine the relationship between work motivation andteamwork performance in the adolescent health outpatient facility care worker around Blitar City.The correlational - cross sectional designwas used. The population were all health professionals who work as PKPR teams in the adolescent health outpatient facility care as intregated health service unit working area of Public Health Department around Blitar City.The total of 30 respondents recruited using total sampling. The Spearman Rho statistical test used to analize the data. The result showed about 18 repondents (60%) had a high work motivation and about 17 respondents (56.7 %) showed good  level of teamwork performance. There is a relationship of work motivation and teamwork performance with p = 0.003 and rs = 0.522. The teamwork performance can reinforce and improved by increasing the motivation of employees. It is recommend to increase the work motivation trough competition and appreciation of the work. The efforts of employee improvement motivation should also be supported within conducive work culture.